Número e tamanho dos recém-nascidos de Hippocampus reidi em ambiente natural - Mai, Ana Cecília Giacometti; Loebmann, Daniel [UNESP] (My University, 2009)
Four births of Hippocampus reidi Ginsburg, 1933 were monitored for the first time under natural conditions. This study provides the fish estimate of fecundity in the wild, which is an important parameter for assessing population dynamics and management strategies.
Size and number of newborn juveniles in wild Hippocampus reidi broods
Keywords: Fecundity; Newborn size; Reproduction; Seahorse; Hippocampus (fish); Hippocampus reidi